THE EFFECT OF UNEMPLOYMENT, PER CAPITA INCOME, LIFE EXPECTANCY, AND EDUCATION LEVEL ON THE HUMAN DEVELOPMENT INDEX IN PANGKEP REGENCY. THESIS. DEVELOPMENT ECONOMICS STUDY PROGRAM, FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS MUHAMMADIYAH MAKASSAR. SUPERVISED BY ISMAIL RASULONG AND NUR ACHSANUDDIN - Muklisa, Muklisa; Rasulong, Ismail; UA, A.nur Achsanuddin (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the effect of unemployment, per capita income, life expectancy, and education level on the Human Development Index (HDI) in Pangkep Regency. This research employed a quantitative method with an associative approach. The data used in this study were secondary data in the form of time-series data from 2015 to 2024, collected through documentation. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 25. The results indicate that unemployment has a negative but not significant effect on the Human Development Index, with a t-value of -1.166 and a significance value of 0.271, which is greater than 0.05. Per capita income has a positive and significant effect on the Human Development Index, with a t-value of 4.055 and a significance value of 0.002, which is less than 0.05. Life expectancy has a significant effect on the Human Development Index, with a t-value of -5.699 and a significance value of < 0.001, which is less than 0.05. Meanwhile, the level of education has a positive and significant effect on the Human Development Index, with a t-value of 4.395 and a significance value of 0.001, which is less than 0.05. These findings indicate that per capita income and education level play an important role in improving the Human Development Index in Pangkep Regency, while unemployment does not have a significant effect on HDI.